Pengaruh Promosi terhadap Impuls Buying dengan Gender sebagai Variabel Dummy - Raafi, Gilang; Martono, S (Management Analysis Journal, 2016)
The purpose of this study are to explain effect of promotion on impuls buying and to explain that woman is more often in doing impuls buying compare to the man. The sampling process was using incidental sampling technique with number of respondents were 100 respondents. Methods of data collection used were observation method, interview method, questionnaire method, and documentation method. Methods of data analysis that had been used were multiple linear regression analysis with dummy variables using SPSS 16.0. The Results of the study show that promotion is directly effect on impuls buying and not proven that woman is more often than man in doing impuls buying. The Conclusions is proven that promotion was directly effect on impuls buying and it is not proven that woman is more often in doing impuls buying compare to man. Suggestions for the company are to increase more interesting promotions and to add more fashion products for man and woman.